2006
DOI: 10.1007/s10637-005-5055-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of irofulven and cisplatin administered in a 30-min infusion every two weeks to patients with advanced solid tumors

Abstract: Irofulven with cisplatin was adequately tolerated and substantial evidence of antitumor activity was observed. The recommended dose is irofulven 0.4 mg/kg and cisplatin 30 mg/m2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…One case of transient grade three blurred vision was reported at DL4 (0.50 mg/kg irofulven), with the remainder of the events restricted to grade 1-2, and resolving in less than 1 week in five patients (start date not available for three patients). Despite reports of capecitabine being associated with visual toxicity (eye irritation, blurred vision, increased tears and decreased visual acuity related to keratitis secondary to corneal deposits of capecitabine) the incidence in this study was no higher than that observed in previous studies of biweekly irofulven over a similar dose range [19]. Grade 1-2 hand-foot syndrome, a characteristic fluoropyrimidine toxicity, was observed in 25% of patients at the RD, without ever reaching grade 3 severity, consistent with the incidence of this toxicity following capecitabine monotherapy at a dose of 2,000 mg/m 2 /day [30], and lower than the 50 to 90% reported for capecitabine administered at a dose of 2,500 mg/m 2 /day for 2 weeks out of every 3 [30,31].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…One case of transient grade three blurred vision was reported at DL4 (0.50 mg/kg irofulven), with the remainder of the events restricted to grade 1-2, and resolving in less than 1 week in five patients (start date not available for three patients). Despite reports of capecitabine being associated with visual toxicity (eye irritation, blurred vision, increased tears and decreased visual acuity related to keratitis secondary to corneal deposits of capecitabine) the incidence in this study was no higher than that observed in previous studies of biweekly irofulven over a similar dose range [19]. Grade 1-2 hand-foot syndrome, a characteristic fluoropyrimidine toxicity, was observed in 25% of patients at the RD, without ever reaching grade 3 severity, consistent with the incidence of this toxicity following capecitabine monotherapy at a dose of 2,000 mg/m 2 /day [30], and lower than the 50 to 90% reported for capecitabine administered at a dose of 2,500 mg/m 2 /day for 2 weeks out of every 3 [30,31].…”
Section: Discussioncontrasting
confidence: 88%
“…Subsequent single-agent studies explored weekly and biweekly schedules of irofulven; the recommended biweekly regimen became 0.5 mg/kg as a 30-min infusion [10,27]. Consequently, the irofulven dose recommended for use in combination with capecitabine represents 80% of the single agent recommended dose for biweekly administration and the same as that recommended for use in combination with cisplatin [19]. The recommended dose of capecitabine in combination with irofulven is also 80% of the single agent dose, 2,500 mg/m 2 /day [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irofulven has demonstrated activity against PC-3 and DU145 cells as monotherapy and enhanced efficacy was displayed in combination with mitoxantrone or docetaxel (Van Laar et al, 2004) and these results highlighted its potential to be used in combination regimens in clinical trials. Thus a phase I and pharmacokinetic study of irofulven (0.4 mg/kg) and cisplatin (30 mg/m 2 ) in patients with solid tumors concluded that the regimen was adequately tolerated with substantial evidence of antitumor activity observed (Hilgers et al, 2006). Combination regiments of the same dosage of irofulven with capecitabine (2,000mg/m 2 /day) were also found safe on phase I clinical trials in patients with solid tumors (Alexandre et al, 2007).…”
Section: Irofulvenmentioning
confidence: 99%